The pedagogical basis of physical education at school - Куспанова, Ақбаян; Сейсенбеков, Ерлан; Елшиев, Балғабай; Юсупалиев, Бердияр; Андақұл, М. (Pedagogy and Psychology, 2020)
The rules for physical education in schools are designated and approved in accordance with the specific conditions, the availability of equipment, equipment, gyms, playgrounds and other facilities of each school. The rules indicate the order of classes, the application of efforts to perform oral and other tasks of the teacher, behavior, a conscientious attitude to orders during physical education classes. Each student must strictly observe the rules of personal and public hygiene. To fulfill the objectives of the school curriculum, students must make every effort to develop motor qualities. It is advisable to ensure the participation of students in all extracurricular and extracurricular physical education and sports events. In general, in order to maintain a healthy lifestyle for each student, teachers are required to develop a comprehensive program to conduct various activities held at the school for the entire academic year. A comprehensive program is developed taking into account the age characteristics of schoolchildren, ranging from primary school to high school students.